Management Strategy for Al-Qur'an Education Parks Based on a Quality Assurance System to Improve Students' Competence in Reading the Al-Qur'an - Achmad Syukri Prihanto; Khoirul Anwar (Global Education Journal, 2026)
Qur'anic Education Centers (Taman Pendidikan Al-Qur'an or TPQ) play a strategic role as non-formal Islamic educational institutions in developing students' competence in reading the Qur'an. This study aims to analyze the management strategies employed by TPQ Nursalam Surakarta to improve students' competence in reading the Qur'an and to identify the supporting and inhibiting factors affecting its management. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation using both primary and secondary data sources. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the management strategy of TPQ Nursalam Surakarta is implemented through systematic learning planning, effective organization of teaching staff, the implementation of Qur'anic learning according to students' competency levels, and periodic evaluation of learning outcomes. These strategies contribute to improving students' competence in terms of reading fluency, accurate pronunciation (makhraj), and the application of tajwid rules. The successful implementation of the management strategy is supported by active participation from the local community, parents, religious leaders, mosque administrators, and local government through both moral and material support. The main challenges include the limited number and competence of teaching staff, inadequate teacher welfare, and insufficient learning facilities and infrastructure. The study concludes that well-planned, participatory, and adaptive management strategies are essential for improving students' competence in reading the Qur'an at TPQ.